Effect of Particle Breakage and Shape on the Mechanical Behaviors of Granular Materials - Yongxin Wang; Shengjun Shao; Zhi Wang (Advances in Civil Engineering)
The particle breakage property under loading is an important factor affecting the nonlinearity of the shear strength and stress-strain curves of coarse-grained soils. The macromechanical behaviors of coarse granular materials under consolidation and drainage shearing were tested by using a large true triaxial apparatus. The particle breakage mechanism has been analyzed by the fluctuation change of stress-strain curve and particle composition change. It was shown that the particle shape is an extremely important microproperty of the influence of granular material breakage. The variation rules of the internal friction angle and interlocking strength with the index of fine-grained breakage were sorted out, and the critical particle size for measuring the two friction modes under the given gradation was determined to be 1 mm. In addition, the numerical analysis was conducted by simulating the microshape parameters of particles. The conclusion is as follows: (1) The effect of shape parameters on shear strength can be simulated using the smoothness index Fd. (2) Compared with spherical particles, irregular-shaped particles lead to a decrease in the number of strong force chains. Moreover, more coordination numbers are needed to maintain a stable configuration, and the shear strength is improved.